Transcriptome Analysis of Liver Cancer Cell Huh-7 Treated With Metformin - Chun-Qing Li; Zhi-Qin Liu; Sha-Sha Liu; Sha-Sha Liu; Gao-Tao Zhang; Li Jiang; Chuan Chen; Du-Qiang Luo (Frontiers Media S.A., 2022)
Metformin is a kind of widely used antidiabetic drug that regulates glucose homeostasis by inhibiting liver glucose production and increasing muscle glucose uptake. Recently, some studies showed that metformin exhibits anticancer properties in a variety of cancers. Although several antitumor mechanisms have been proposed for metformin action, its mode of action in human liver cancer remains not elucidated. In our study, we investigated the underlying molecular mechanisms of metformin's antitumor effect on Huh-7 cells of hepatocellular carcinoma (HCC) in vitro. RNA sequencing was performed to explore the effect of metformin on the transcriptome of Huh-7 cells. The results revealed that 4,518 genes (with log2 fold change > 1 or < −1, adjusted p-value < 0.05) were differentially expressed in Huh-7 cells with treatment of 25-mM metformin compared with 0-mM metformin, including 1,812 upregulated and 2,706 downregulated genes. Gene ontology and Kyoto Encyclopedia of Genes and Genomes pathway analyses identified 54 classical pathways that were significantly enriched, and 16 pathways are closely associated with cancer, such as cell cycle, DNA replication, extracellular matrix-receptor interaction, and so on. We selected 11 differentially expressed genes, which are closely associated with HCC, to validate their differential expressions through a quantitative real-time reverse transcription-polymerase chain reaction. The result exhibited that the genes of fatty acid synthase, mini-chromosome maintenance complex components 6 and 5, myristoylated alanine-rich C-kinase substrate, fatty acid desaturase 2, C-X-C motif chemokine ligand 1, bone morphogenetic protein 4, S-phase kinase-associated protein 2, kininogen 1, and proliferating cell nuclear antigen were downregulated, and Dual-specificity phosphatase-1 is significantly upregulated in Huh-7 cells with treatment of 25-mM metformin. These differentially expressed genes and pathways might play a crucial part in the antitumor effect of metformin and might be potential targets of metformin treating HCC. Further investigations are required to evaluate the metformin mechanisms of anticancer action in vivo.